Red Cell Glucose 6-Phosphate Dehydrogenase Deficiency in the Northern Region of Turkey: Is G6PD Deficiency Exclusively a Male Disease?. (1st March 2015) - Albayrak, Canan; Albayrak, Davut
Abstract : Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked recessive genetic defect that can cause hemolytic crisis. However, this disease affects both males and females. In Turkey, the frequency of this enzyme deficiency was reported to vary, from 0.25 to 18%, by the geographical area. Its prevalence in the northern Black Sea region of Turkey is unknown. The aims of this study were to assess the prevalence of G6PD deficiency in the northern region Turkey in children and adults with hyperbilirubinemia and hemolytic anemia. This report included a total of 976 G6PD enzyme results that were analyzed between May 2005 and January 2014. G6PD deficiency was detected in 5.0% of all patients. G6PD deficiency was significantly less frequent in females (1.9%, 6/323) than in males (6.6%, 43/653). G6PD deficiency was detected in 3.7% of infants with hyperbilirubinemia, 9.2% of children, and 4.5% of adults with hemolytic anemia. In both the newborn group and the group of children, G6PD deficiency was significantly more frequent in males. In the combined group of children (groups I and II), the proportion of males was 74% and 67% in all groups ( P = .0008). In conclusion, in northern region of Turkey, G6PD deficiency is an important cause of neonatal hyperbilirubinemia and hemolytic crisis in children and adults. This study suggests that most pediatricians thought that G6PD deficiency is exclusively a male disease. For this reason, some female patients may have been undiagnosed.